Anti-cancer activity of сuraxin CBL0137 on the models of acute leukemia in vitro - T. I. Fetisov; K. I. Kirsanov; A. A. Borunova; M. N. Zatsepina; E. A. Lesovaya; T. N. Zabotina; G. A. Belitsky; M. G. Yakubovskaya (Успехи молекулярной онкологии)
Background. Curaxin CBL0137 is a novel non-genotoxic compound with anti-cancer activity based on CBL0137 ability of non-covalent interaction with DNA causing histone chaperone FACT relocation. Anti-cancer activity of this drug was demonstrated previously on the wide panel of solid cancer models in vitro and in vivo.Objectives. Estimation of anticancer effects of CBL0137 on the acute myeloblastic leukemia cells (THP-1) and acute lymphoblastic leukemia (CCRF-CEM).Materials and methods. CBL0137 cytotoxicity was analyzed using the MTT test, the effects on the cell cycle and the induction of apoptosis was assessed by flow cytometry, the activity of signaling pathways in cells treated with CBL0137 was determined by real-time polymerase chain reaction.Results. Cell treatment with CBL0137 led to cell cycle arrest and apoptosis induction. In the study of CBL0137 effect on target gene clusters of 10 signal transduction pathways involved in the pathogenesis of acute leukemia we have showed that CBL0137 inhibited the expression of down-stream genes of WNT and Hedgehog signaling in both cell lines. In THP-1 cells we also observed the inhibition of the expression of PPARγ target and hypoxia-activated genes. In CCRF-CEM cells CBL0137 also induced the expression of Notch signaling target genes.Conclusion. The antitumor activity of CBL0137 was demonstrated on acute leukemia cell cultures, the drug possesses cytotoxicity, causes cell cycle arrest and activation of apoptosis. Significant changes in the expression of efferent gene clusters of several signaling pathways were observed in the cells treated with CBL0137.